Antibody Engineering Volume 2 - Kontermann, Roland E.; Dübel, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Antibodies are indispensable tools for research, diagnosis, and therapy. Recombinant approaches allow the modification and improvement of nearly all antibody properties, such as affinity, valency, specificity, stability, serum half-life, effector functions, and immunogenicity. Antibody Engineering provides a comprehensive toolbox covering the well-established basics but also many exciting new techniques. The protocols reflect the latest "hands on" knowledge of key laboratories in this still fast-moving field. Newcomers will benefit from the proven step-by-step protocols, which include helpful practical advice; experienced antibody engineers will appreciate the new ideas and approaches. The book is an invaluable resource for all those engaged in antibody research and development.
Bioinformatics of Antigen-binding Sites -- Analysis of Single Chain Antibody Sequences Using the VBASE2 Fab Analysis Tool -- Standardized Sequence and Structure Analysis of Antibody Using IMGT® -- Protein Sequence and Structure Analysis of Antibody Variable Domains -- Generation of Antibody Fragments and Their Derivatives -- scFv by Two-Step Cloning -- Bivalent Diabodies -- Generation of Single-Chain Fv Fragments and Multivalent Derivatives scFv-Fc and scFv-CH3 (Minibodies) -- Miniantibodies -- Generation of Stably Transfected Eukaryotic Cell Lines Producing ImmunoRNAse Fusion Proteins -- Antibody–Cytokine Fusion Proteins with Members of the TNF-Family -- Recombinant Immunotoxins for Treating Cancer -- T Bodies -- Expressing Intrabodies in Mammalian Cells -- Phenotypic Knockdown with Intrabodies -- Disulfide-Stabilized Fv Fragments -- PEGylation of Antibody Fragments to Improve Pharmacodynamics and Pharmacokinetics -- Fusion Proteins with Improved PK -- In Vivo Biotinylated scFv Fragments -- Bispecific Diabodies and Single-Chain Diabodies -- Generation and Characterization of a Dual Variable Domain Immunoglobulin (DVD-Ig™) Molecule -- Isolation of Antigen-Specific Nanobodies -- CDR-FR Peptides -- Production of Antibody Fragments -- Purification and Characterization of His-Tagged Antibody Fragments -- Production of Antibody Fragments in the Gram-Positive Bacterium Bacillus megaterium -- Analysis and Purification of Antibody Fragments Using Protein A, Protein G, and Protein L -- Purification and Analysis of Strep-tagged Antibody-Fragments -- Production of Antibodies and Antibody Fragments in Escherichia coli -- Improving Expression of scFv Fragments by Co-expression of Periplasmic Chaperones -- Bioreactor Production of scFv Fragments in Pichia pastoris -- Expression of Antibody Fragments in Transgenic Plants -- Transient Production of scFv-Fc Fusion Proteins in Mammalian Cells -- Recombinant Antibody Molecules in Nanobiotechnology and Proteomics -- Immunoliposomes -- Targeted Polymeric Nanoparticles -- Antibody Microarrays for Expression Analysis -- Evaluation of Recombinant Antibodies on Protein Microarrays Applying the Multiple Spotting Technique -- Preclinical and Clinical Development -- Xenograft Mouse Models for Tumour Targeting -- Xenograft Mouse Models for Tumour Targeting -- Imaging Tumor Xenografts Using Radiolabeled Antibodies -- Human Anti-antibody Response -- IP Issues in the Therapeutic Antibody Industry.
Keywords: Immunology; Antibodies; Immunology; Antibodies